2021
DOI: 10.1016/j.arbres.2021.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Protective Recommendations for Non-invasive Ventilation During COVID-19 Pandemic: A Bench Evaluation of the Effects of Instrumental Dead Space on Alveolar Ventilation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(23 reference statements)
1
4
0
1
Order By: Relevance
“…In line with previous bench studies [ 3 , 11 ], our results highlight that PAP and NIV devices should be used as per their user manual without any alteration on their regular setup. Indeed, any change may impair their efficacy.…”
supporting
confidence: 90%
“…In line with previous bench studies [ 3 , 11 ], our results highlight that PAP and NIV devices should be used as per their user manual without any alteration on their regular setup. Indeed, any change may impair their efficacy.…”
supporting
confidence: 90%
“…Furthermore, the instrumental dead space effect on alveolar ventilation should be pondered. In a bench study, Delorme et al , demonstrated that when the dual-limb circuit was connected to a non-vented mask with two filters placed both at the inspiratory and expiratory port of the ventilator, the dead space effect was low [ 71 ]. The disadvantages and advantages of different tubing systems equipped with BVF, HME and HMEF are shown in figure 1 .…”
Section: Prudently Applying Non-invasive Respiratory Support (Nirs)mentioning
confidence: 99%
“…Delorme et al , compared the effects on dead space and P ETCO2 in differently deployed NIPPV. In methods b and c, pressure support levels had to be increased to 6 and 1cmH2O respectively to compensate for the equipment dead space [ 71 ]. A dual-limb circuit connected to a non-vented mask (e) is the best recommendation and (c) and (d) are recommended if a single-limb circuit was applying.…”
Section: Prudently Applying Non-invasive Respiratory Support (Nirs)mentioning
confidence: 99%
“… 12 , 13 , 14 , 15 , 16 Finally, many treatments both pharmacological (especially antivirals, immunomodulators and anti-inflammatories) and non-pharmacological treatments has been used during this pandemic era at different moments and severities of the disease, sometimes with controversial results. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 …”
Section: Introductionmentioning
confidence: 99%